2017
DOI: 10.1111/cge.13065
|View full text |Cite
|
Sign up to set email alerts
|

Performance of BRCA1/2 mutation prediction models in male breast cancer patients

Abstract: To establish whether existing mutation prediction models can identify which male breast cancer (MBC) patients should be offered BRCA1 and BRCA2 diagnostic DNA screening, we compared the performance of BOADICEA (Breast and Ovarian Analysis of Disease Incidence and Carrier Estimation Algorithm), BRCAPRO (BRCA probability) and the Myriad prevalence table ("Myriad"). These models were evaluated using the family data of 307 Dutch MBC probands tested for BRCA1/2, 58 (19%) of whom were carriers. We compared the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Also, information about risk-reducing surgery in family members may not necessarily be available in the clinic. Due to few cases, the present study did not evaluate male breast cancer separately, but a validation study focused on this group of patients has previously demonstrated acceptable performance of the model for BRCA1 and BRCA2 37 . Multifactorial risk factors and polygenic risk scores were not included in the present validation but could potentially improve the performance of the model.…”
Section: Discussionmentioning
confidence: 99%
“…Also, information about risk-reducing surgery in family members may not necessarily be available in the clinic. Due to few cases, the present study did not evaluate male breast cancer separately, but a validation study focused on this group of patients has previously demonstrated acceptable performance of the model for BRCA1 and BRCA2 37 . Multifactorial risk factors and polygenic risk scores were not included in the present validation but could potentially improve the performance of the model.…”
Section: Discussionmentioning
confidence: 99%
“…BRCAPRO is a validated tool (32) commonly used by genetic counselors to assess a proband's carrier probability to inform mutation testing decision-making (see Supplementary Methods). BRCAPRO uses a variety of information from probands and the entire reported family history (33,34); its calibration has been widely studied in various populations and types of probands (35)(36)(37)(38). BRCAPRO is similar to the BOADICEA (39) model.…”
Section: Calculating Carrier Probability With Brcapromentioning
confidence: 99%